Produção científica docente em tratamento temático da informação nos cursos de Biblioteconomia do Mercosul: uma análise preliminar - Danuello, Jane Coelho [UNESP]; Guimarães, José Augusto Chaves [UNESP] (Pontifícia Universidade Católica de Campinas, 2005)
The educational discussions on subject treatment of information that have been taking place since 1996 during the annual meetings of the Mercosul Library Schools, have encouraged the first round of analysis of the disciplines' contents and bibliographies. Such an investigation showed a wide variety of subject treatment of information theoretical influences among the distinct Library Schools. It leaded to the need of investigating the scientific production of the subject treatment of information professors in order: a) to verify the subject coherence between the bibliography used by docents in their pedagogical practices, and their own scientific production; b) to analyze their scientific contribution through their scientific production; c) to identify subject treatment of information invisible colleges at the Mercosul area; d) to contribute to the task force studies on information organization and retrieval of the Mercosul Library Schools Group. This literature revision on subject treatment of information education at Mercosul, as well as on scientific production, has supported the data collecting among professors from 28 Library Schools, which obtained a return of 68.85% of that universe. Results showed that only 12 professors, from 5 universities are responsible for 91.57% of the whole scientific production (whole books, book chapters, articles in journals and conference proceedings). It was also verified a relative balance among the number of proceedings, articles and monographic publications (books and chapters) whose medium life is around 6 years (considered a good level, by the area standards). When comparing the individual bibliographies used by the disciplines' professors with the bibliography of their own scientific production, it was verified that only 13.25% of the items in the latter were present in the disciplines' bibliographies. In conclusion, these results reveal that the subject treatment of information scientific production of Mercosul Library Schools has mainly been the output of a small group of scholars, mostly PhD professors from universities which offer both undergraduate and graduate (masters´ and doctorate´ s degrees) programs. Furthermore, they reveal that the presence of such production as research source in the individual bibliographies of the area disciplines is still modest. Such results demonstrate the urgent need to promote scientific exchange and partnership programs among subject treatment of information professors at the Mercosul area, in order to encourage them to form invisible colleges, as well as to make their scientific production more visible to the Educational environment.

As discussões sobre ensino de Tratamento Temático da Informação ocorridas desde 1996 nos encontros anuais do grupo de escolas de Biblioteconomia do Mercosul motivaram, em uma primeira fase, a análise dos conteúdos básicos das disciplinas da área e da bibliografia utilizada nessas disciplinas, constatando-se haver grande diversidade de linhas teóricas entre os docentes da área. Desse modo, sentiu-se a necessidade de investigar a produção científica desses docentes, propiciando um cotejo preliminar ensino/pesquisa na área, no Mercosul, buscando: a) verificar a coerência temática existente entre a bibliografia utilizada na prática pedagógica e a produção científica desses docentes; b) analisar a contribuição do segmento docente para o cenário científico da área, como subsídio para o incentivo ao intercâmbio de produção científica gerada na área, na região; c) lançar bases para a identificação de colégios invisíveis na área; e d) contribuir com os estudos curriculares do Grupo de Trabalho em Organização e Tratamento da Informação do Mercosul. Para tanto, realizaram-se as revisões da literatura sobre o ensino de Tratamento Temático da Informação no Mercosul e sobre a produção científica dos docentes, seguida de coleta de dados por meio de questionários que foram enviados aos docentes das 28 instituições que compuseram o universo da fase anterior da pesquisa, obtendo-se um índice de respostas de 67,85%. A análise da produção dos docentes (restrita a livros, capítulos de livros, artigos de periódicos e publicações na íntegra em eventos) demonstrou que 91,57% das publicações na área estão a cargo de 12 docentes de apenas cinco universidades, revelando que o grupo mais produtivo compõe-se de 66,67% dos docentes e 31,25% das instituições. Quanto à forma, observa-se um equilíbrio entre publicações em eventos, artigos de periódicos e literatura monográfica (livros e capítulos de livros). Verificou-se, ainda, que apenas 22 itens (13,25%) da produção dos docentes na área de Tratamento Temático da Informação, encontram-se presentes na bibliografia utilizada nas disciplinas por eles ministradas, revelando uma contribuição ainda modesta para a construção das fontes de pesquisa para a área.
Scientific production on subject treatment of information in Library Schools' programs of Mercosul: a preliminary analysis
Keywords: ensino de biblioteconomia; produção científica; tratamento temático da informação; Mercosul; library education; scientific production; subject treatment of information; Mercosul